GENDER ASPECTS OF PUBLIC-PRIVATE PARTNERSHIP IN SMALL AND MEDIUM BUSINESS - Lukin , S. Yu; Meliakov , A. V.; Baklan , A. O (Theory and Practice of Public Administration, 2021)
In the public and scientific spaces, there is a growing interest in the issue of women’s entrepreneurship. The business activity of our compatriots is increasingly the focus of economists, sociologists, psychologists, experts in the field of gender studies, women’s studies and more. Much less attention is paid to the management aspect of the topic, which involves identifying the most effective tools for women’s business associations to interact with the executive and local governments. In order to accumulate and further develop expert opinion, the authors of the article conducted a survey in the form of personal interviews in May 2021. Among the current problems, the solution of which is the aim of the leading women’s business community of modern Ukraine efforts, experts note: the practice of “manual” regulation of economic processes by government agencies; secrecy of information necessary for full-fledged business activity of SME representatives; unpredictability and a certain chaos of changes in national legislation; lack of proper communication between local state administrations and business structures, even when working out documents that determine the socio-economic development of the region / community (target programs, strategies, concepts, etc.). Combating unscrupulous employers, illegal business, illegal labor practices, etc. should be a mandatory component of the interaction of business associations with the authorities. The majority of respondents positively assess the opportunities and prospects of doing business in Ukraine and do not see real grounds for its division into purely “female” and “male”. At the same time, business communities are not only a useful business institution, but also form a model of “proper synergy”. Entrepreneurs are trying to “find themselves” not only in sectors such as direct sales, hotel and restaurant services, retail, fitness and beauty industry. The positions of business women in the agricultural sector, IT industry, energy, real estate, metallurgy, etc. are becoming more and more noticeable. The age limits of the business women circle are also expanding, both at the expense of very young entrepreneurs who are taking their first steps in business in the first year of university, and women of the “golden age” who prove by personal success that active entrepreneurship is the best guarantee against ageism. According to experts, the key to successful SME development should be active and systematic lobbying of business interests to the authorities at all levels, adherence to the principles of social responsibility, continued efforts to create equal opportunities for men and women, the ability of individual women’s societies to unite around constructive and consolidating ideas. Also, experts state that the indispensable condition for successful business is borrowing and mastering the best connections of foreign experience, so it becomes important to study the practical cases of women’s entrepreneurship in Central and Eastern Europe. Women’s business associations must play a significant role in achieving these goals.